Should We Bother With “Theories of the Emotions”? - Carty, Alexander (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
Christine Tappolet’s Philosophy of Emotion: A Contemporary Introduction is a comprehensive inventory of recent developments in the philosophy of emotion. Part 2 of the book examines various theories that answer the first question from chapter 1: What is the essence of emotions? My commentary compares these theories with Amélie Oksenberg Rorty’s argument for a skeptical answer to this question.